(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Ischemic heart disease (IHD) remains one of the most significant causes of morbidity and mortality globally, accounting for more than 14 million deaths per year (WHO) [1]. At the same time, chronic oral diseases—particularly periodontal disease, dental caries, and oral mucosal lesions—represent widespread inflammatory conditions that affect a majority of the adult population worldwide [2]. Contemporary research has demonstrated a bidirectional relationship between periodontal inflammation and cardiovascular pathology, where oral microbial endotoxins and pro-inflammatory mediators accelerate endothelial dysfunction and contribute to atherosclerosis progression [3,4].